1996
DOI: 10.1096/fasebj.10.11.8836047
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide and hydrogen peroxide‐dependent inhibition of iron regulatory protein activity: a protective stratagem against oxidative injury

Abstract: Cellular iron homeostasis is regulated by the cytoplasmic iron regulatory protein (IRP), which binds to iron-responsive elements (IRE) of mRNAs, modulating iron uptake and sequestration, respectively. When iron is scarce, IRP binds to IRE and coordinately increases the synthesis of transferrin receptor and decreases that of ferritin, thus providing the cell with readily available free iron. When iron is in excess, IRP does not bind and iron sequestration prevails over iron uptake. We have found that incubation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
80
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 119 publications
(82 citation statements)
references
References 22 publications
2
80
0
Order By: Relevance
“…[23][24][25] Both in vitro and in vivo studies have shown that a number of conditions or agents known to increase cellular levels of ROS induce the reversible inactivation of IRP-1 aimed at decreasing TfR-1 levels while also increasing ferritin levels and hence diminishing the LIP. [26][27][28][29][30] To define that TfR-1 is related with LIP accumulation in CCA, we detected TfR-1 expression and LIP accumulation in CCA cell lines compared with immortal cholangiocyte cell line. Our results showed that TfR-1 expression and LIP levels were significantly increased in CCA cell lines than in the cholangiocyte cell line, suggesting that TfR-1 may be associated with iron uptake and hence induce LIP in CCA.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25] Both in vitro and in vivo studies have shown that a number of conditions or agents known to increase cellular levels of ROS induce the reversible inactivation of IRP-1 aimed at decreasing TfR-1 levels while also increasing ferritin levels and hence diminishing the LIP. [26][27][28][29][30] To define that TfR-1 is related with LIP accumulation in CCA, we detected TfR-1 expression and LIP accumulation in CCA cell lines compared with immortal cholangiocyte cell line. Our results showed that TfR-1 expression and LIP levels were significantly increased in CCA cell lines than in the cholangiocyte cell line, suggesting that TfR-1 may be associated with iron uptake and hence induce LIP in CCA.…”
Section: Discussionmentioning
confidence: 99%
“…Ferritin serves as a cytoprotective agent against oxidative stress (8), and iron delivered by TfRs or by airborne particles can increase oxidative stress (7,26). Thus repeated exposure of lung tissues to low levels of smoke as are present in environmental pollutants could result in reduced cytoprotection by ferritin at a time when iron uptake is sustained and ROS are present.…”
Section: Discussionmentioning
confidence: 99%
“…146 Oxidative stress can also contribute to ferritin induction by inactivating IRP1 through reversible oxidation of critical cysteine residues. 147 However, oxidant-mediated inactivation of IRP1 is not always seen. In fact, in other experimental systems, oxidants had the opposite effect: hydrogen peroxide activated the iron responsive protein (IRP1), possibly through induction of a signaling pathway that mobilizes iron from the 4Fe-4S cubane cluster.…”
Section: Ferritin Regulation By Oxidantsmentioning
confidence: 99%